AN ANALYSIS OF SPEAKING DIFFICULTIES FACED BY THE THIRD YEAR STUDENTS OF ENGLISH DEPARTMENT FKIP UNIVERSITAS RIAU - Nadila, Ayu; Azhar, Fadly; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to find out speaking difficulties faced by the third year students of English Department FKIP Universitas Riau. This research is descriptive research that has one variable. The numbers of sample are 30 students chosen by using proportional sampling techniques. To find the difficulties in speaking of the students, there was a questionnaire used for collecting the data. The questionnaire was adapted from Verapornvanichkul (2011). The questionnaire consists of two aspects; linguistics problems (vocabulary, grammar and pronunciation), and psychological problems (fear of making mistakes, anxiety, shyness, lack of confidence and lack of motivation). The questionnaire was accessed by the students online via Google forms. The questionnaire of this research was presented using 5 point Likert-scale start from strongly agree to strongly disagree. The result showed that every student encounter each difficulties of speaking according to the aspect of linguistics and psychological. The mostly difficulties in speaking faced by the student in linguistic aspects is vocabulary (76.6%) and anxiety as the psychological aspect (82%).Key Words: Analysis, Speaking, Speaking Difficulties